Gastric microbiota in the functional dyspepsia patients treated with probiotic yogurt. Issue 1 (1st September 2016) - Nakae, Hirohiko; Tsuda, Ayumi; Matsuoka, Takashi; Mine, Tetsuya; Koga, Yasuhiro
Abstract : Objective: To investigate the structure of the gastric microbiota in functional dyspepsia (FD) and its role in the pathophysiology. Design: We compared the basic physiological properties of the gastric fluid (GF) and the structure of the microbiota in the GF of 44 healthy control (HC) participants and 44 patients with FD. We then treated the patients with FD with a yogurt containing a probiotic strain of Lactobacillus gasseri OLL2716 (LG21 yogurt) and investigated the effects on the bacteriological parameters and symptoms to examine the relationship between them. Results: The volume of GF recovered from the stomach after overnight fasting was greater in the patients with FD than in the HCs, and decreased in the patients with FD whose symptoms were improved by the LG21 yogurt treatment. An analysis using a terminal restriction fragment polymorphism method demonstrated that the overall structure of the bacterial community and the abundance of genus Prevotella in the GF of the patients in the FD group were significantly different from those in the HC group. In the patients with FD, this bacteriological change was restored by treatment with LG21 yogurt. A significant inverse correlation was found between the abundance of Prevotella and the severity of postprandial distress-like symptoms in patients with FD who received LG21 yogurt. Conclusions: Significant dysbiosis was found in the GF microbiota of patients with FD and considered to be involved in the pathogenesis. The abundance of genus Prevotella in the GF may be used as a biomarker of the efficacy of the treatment of FD. Trial registration number: UMINCTR000022026.